The use of herbal and dietary supplements for COVID-19 prevention: a survey among the public in a Malaysian suburban town - Abd Wahab, Mohd Shahezwan; Hamdi, Humaira’; Ali, Aida Azlina; Karuppannan, Mahmathi; Zulkifli, Muhammad Harith; Maniam, Sandra; Ung, Carolina Oi Lam (Elsevier, 2023)
Introduction: The spread of the novel coronavirus disease (COVID-19) may lead people to seek preventative measures. The use of herbal and dietary supplements (HDS) may have become prevalent during the COVID-19 pandemic. This study aims to identify the prevalence, predictors, and patterns of HDS use for COVID-19 prevention in a sample of the general public in a suburban town in Malaysia. Methods: An online cross-sectional survey was conducted between May and June 2021 involving adults ≥ 18 years old. Data on the self-reported use of HDS for COVID-19 prevention were collected. Logistic regression analysis was conducted to determine the predictors of HDS use. Results: Overall, 41.9 % (168/401) reported using HDS to prevent COVID-19. Multivariate analysis showed that HDS users were more likely to be individuals ≥ 40 years old (adjusted odds ratio [aOR] = 1.774, 95 % confidence interval [CI] = 1.016 – 3.098), and to have had a history of HDS use prior to the pandemic (aOR = 19.378, 95 % CI = 5.901 – 63.639). Most HDS users referred to social media or websites (66.7 %, 112/168) for HDS information. Approximately half of them had consulted either pharmacists or doctors about their HDS use. Conclusion: HDS use to prevent COVID-19 was common among the respondents. Several issues - such as the concurrent use of HDS with conventional medications, the use of unreliable sources of information, and the lack of consultation with healthcare providers (HCPs) - indicate that HCPs should be more proactive in their consultative and information-providing roles regarding HDS use.